2020
DOI: 10.1002/wrna.1584
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs: New regulatory code in chondrocyte apoptosis and autophagy

Abstract: Osteoarthritis (OA) is a bone and joint disease characterized by progressive cartilage degradation. In the face of global trends of population aging, OA is expected to become the fourth most common disabling disease by 2020. Nevertheless, the detailed pathogenesis of OA has not yet been elucidated. Noncoding RNAs (ncRNAs), including long noncoding RNAs, microRNAs, and circular RNAs, do not encode proteins but have recently emerged as important regulators of apoptosis and autophagy of chondrocytes, thereby high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 171 publications
0
37
0
1
Order By: Relevance
“…Qian et al [ 46 ] found that the lnc-HLA-DQA1-5 (ENST00000419852, HLA-DQB1-AS1) expression in patients with smoking chronic obstructive pulmonary disease (COPD) was increased compared to controls and speculated that it played a crucial role in the pathogenesis in smoking COPD. Admittedly, accumulating evidence supported that there were many differentially expressed lncRNAs in KOA cartilage [ 35 , 47 ] and that lncRNAs were involved in the formation, proliferation, apoptosis, and autophagy of chondrocytes [ 47 , 48 ]. For example, FOXD2-AS1 induced the proliferation of chondrocytes in OA by sponging miR-27a-3p [ 49 ], lncRNA-CIR regulated the apoptosis of chondrocytes in OA [ 50 ], and overexpression of lncRNA-ROR significantly promoted the viability of OA chondrocytes and regulated the autophagy and apoptosis of chondrocytes through p53 and HIF1 α [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qian et al [ 46 ] found that the lnc-HLA-DQA1-5 (ENST00000419852, HLA-DQB1-AS1) expression in patients with smoking chronic obstructive pulmonary disease (COPD) was increased compared to controls and speculated that it played a crucial role in the pathogenesis in smoking COPD. Admittedly, accumulating evidence supported that there were many differentially expressed lncRNAs in KOA cartilage [ 35 , 47 ] and that lncRNAs were involved in the formation, proliferation, apoptosis, and autophagy of chondrocytes [ 47 , 48 ]. For example, FOXD2-AS1 induced the proliferation of chondrocytes in OA by sponging miR-27a-3p [ 49 ], lncRNA-CIR regulated the apoptosis of chondrocytes in OA [ 50 ], and overexpression of lncRNA-ROR significantly promoted the viability of OA chondrocytes and regulated the autophagy and apoptosis of chondrocytes through p53 and HIF1 α [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of circRNAs in the pathogenesis of OA has drawn increasing attention (17,27,28). Previous studies revealed that circRNAs play regulatory roles in cartilage ECM degradation, in ammatory response in chondrocytes, and apoptosis (12,29). This study investigated the pathogenesis of OA from the perspective of the regulation of HA metabolism by circRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, once the tumor is formed, autophagy plays an oncogenic function that provides cancer cells with needed survival contexts, such as nutrition to resist stress (especially after chemotherapy treatment) (Kimmelman and White, 2017). The specific roles of autophagy in tumors depend on tumor type and tumor heterogeneity, which is regulated by multiple proteins and non-coding RNAs (ncRNAs) (Jiang et al, 2020;Perez-Montoyo, 2020).…”
Section: Introductionmentioning
confidence: 99%